The Effect Of Play Approach On Gross Motor Skills Of Disability Children In SLB Jombang Regency - Rendra, Rendra; Nurhasan, Nurhasan; Suroto, Suroto; Wahyu Hidayat, Zakaria (International Journal of Educational Research & Social Sciences, 2023)
Based on the purpose of this study to get an overview of the play approach to gross motor skills of children with disabilities, using a method for this study with Pre-Experimental Design, this research design with pretest and post-test. Retrieval using tests related to motor movement skills. The number of subjects used in the study were 27 students of tunagrahita children. Data analysis techniques using descriptive statistics are used to interpret and analyse data and t-test to see significant differences in the two variables before and after the play approach. The results of the calculation of the pre-test score description minimum score 7, maximum 12 average 8.74, standard deviation 1.28, for the post test score minimum 7, maximum 15, average 12.22, standard deviation 1.82. For the calculation of the difference test between the post test and the pre test using the paired sample test, the value based on the sig value is 0.00 <0.05, so it can be concluded that there is an effect of the play approach on the motor skills of children with disabilities in SLB Jombang Regency